2019
DOI: 10.14814/phy2.14226
|View full text |Cite
|
Sign up to set email alerts
|

Divergent paths to seizure‐like events

Abstract: Much debate exists about how the brain transitions into an epileptic seizure. One source of confusion is that there are likely to be critical differences between experimental seizure models. To address this, we have compared the evolving activity patterns in two widely used in vitro models of epileptic discharges. Brain slices from young adult mice were prepared in the same way and bathed either in 0 Mg2+ or 100 µmol/L 4AP artificial cerebrospinal fluid. We have found that while local field potential recording… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 71 publications
2
37
0
Order By: Relevance
“…In this study, we found no significant effect of epileptiform activity on the passive membrane properties or firing properties of CA1 hippocampal neurons, although some studies have shown such changes. For example, 4-AP-induced epileptiform activity in the neocortex increased input resistance of parvalbumin-expressing neurons and reduced the action potential threshold for parvalbumin-expressing and pyramidal neurons both [43]. Apart from the 4-AP model, an increase in input resistance has been observed in the CA1 neurons of genetically epilepsy-prone rats [44], kindled rats [45], and in the pentylenetetrazole model [17].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found no significant effect of epileptiform activity on the passive membrane properties or firing properties of CA1 hippocampal neurons, although some studies have shown such changes. For example, 4-AP-induced epileptiform activity in the neocortex increased input resistance of parvalbumin-expressing neurons and reduced the action potential threshold for parvalbumin-expressing and pyramidal neurons both [43]. Apart from the 4-AP model, an increase in input resistance has been observed in the CA1 neurons of genetically epilepsy-prone rats [44], kindled rats [45], and in the pentylenetetrazole model [17].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found no significant effect of epileptiform activity on the passive membrane properties or firing properties of CA1 hippocampal neurons, although some studies have shown such changes. For example, 4-AP-induced epileptiform activity in the neocortex increased input resistance of parvalbumin-expressing neurons and reduced the action potential threshold for parvalbumin-expressing and pyramidal neurons both [42]. Apart from the 4-AP model, an increase in input resistance has been observed in the CA1 neurons of genetically epilepsy-prone rats [43], kindled rats [44], and in the pentylenetetrazole model [17].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, several groups have demonstrated the coordination of interneuronal activation across single gap junctions (Galarreta and Hestrin, 1999;Gibson et al, 1999), but for more extensive propagation within cortical networks, gap junction-facilitated propagation over extended distances has only been demonstrated using pharmacological manipulation, bathing tissue in 4-AP (Szente et al, 2002;Gajda et al, 2003;Gigout et al, 2006a). This pharmacological manipulation, while of interest, does represent a rather extreme disruption of neocortical interneuron behavior (Codadu et al, 2019a). Of particular relevance to the present study is that 4-AP makes neurons more electrotonically compact, by blocking a large component of K 1 conductance, and will thus naturally facilitate electrotonic propagation.…”
Section: Discussionmentioning
confidence: 99%
“…Since 4-AP has a disproportionately large effect on the population of parvalbumin-expressing interneurons (Codadu et al, 2019a), we also chose to study the effect of raised [K 1 ] o in this same population. Electrical coupling between this population of interneurons is well established (Galarreta and Hestrin, 1999;Gibson et al, 1999), but coupling has also been described for other populations of cortical interneurons (Galarreta and Hestrin, 2001;Hestrin and Galarreta, 2005), and our findings are likely to generalize to these interneuronal populations too.…”
Section: Discussionmentioning
confidence: 99%